Uji Stabilitas Kimia Natrium Askorbil Fosfat Dalam Mikroemulsi Dan Analisisnya Dengan HPLC - Deviarny, Chris; Lucida, Henny; Safni, Safni (Jurnal Farmasi Andalas, 2013)
It has been tested the influence of pH, the influence of microemulsion types and the influence of storage temperature on the stability of natrii ascorbyl phosphate (which is often known as Sodium Ascorbyl Phosphate/SAP) and analysis using HPLC method. Kinetics test carried out by dissolving the SAP in a buffer solution with different pH, namely: 4.5: 5.5: 6.5 and 7.5 at a temperature of 300C and 400C. SAP decomposes according to first-order kinetics (y = -0.0027 x - 3.5224 and r = 0.9546, price the value of k = 6.2181 x 10-3 per minute) with a slow rate of decomposition at pH 6.5. Furthermore, SAP isformulated in the preparation of microemulsion type of M/A and A/M with anoptimum pH conditions for SAP, then tested the stability of SAP with SAP store at temperatures 300C and 400C for one week. The remaining levels of SAP werecalculated and analyzed by one-way T-tested method. Showed that the type of chemical stability of microemulsions affect SAP which is morestable in the microemulsion type of M/A.